2013
DOI: 10.1038/srep03529
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric CT-based segmentation of NSCLC using 3D-Slicer

Abstract: Accurate volumetric assessment in non-small cell lung cancer (NSCLC) is critical for adequately informing treatments. In this study we assessed the clinical relevance of a semiautomatic computed tomography (CT)-based segmentation method using the competitive region-growing based algorithm, implemented in the free and public available 3D-Slicer software platform. We compared the 3D-Slicer segmented volumes by three independent observers, who segmented the primary tumour of 20 NSCLC patients twice, to manual sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 28 publications
2
138
0
5
Order By: Relevance
“…7 To overcome this methodological shortcoming, we used the interactive GrowCut algorithm implemented in the 3D Slicer. Velazquez et al 26 have shown some robust results for CT-based segmentation of NSCLC and we tried to extend it to segment the functional volume from FDG PET images. However, the algorithm is dependent on the correctness of user-marked labels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 To overcome this methodological shortcoming, we used the interactive GrowCut algorithm implemented in the 3D Slicer. Velazquez et al 26 have shown some robust results for CT-based segmentation of NSCLC and we tried to extend it to segment the functional volume from FDG PET images. However, the algorithm is dependent on the correctness of user-marked labels.…”
Section: Discussionmentioning
confidence: 99%
“…An uncertainty region, as described in Ref. 26, was calculated as the difference between the union and intersection volumes of the three runs (represented as A, B, and C) for the GrowCut and IGC segmentation methods:…”
Section: Repeatability Of Improved Growcut and 3dmentioning
confidence: 99%
“…They evaluated the predictive values of more than 400 textural and shape-and intensity-based features extracted from the computed tomography (CT) images acquired before treatment. Tumor volumes were delineated either by radiation oncologists or using semiautomatic segmentation methods [16,17]. A subset of radiomic features were identified for predicting patient survival and describing intra-tumoral heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Using 3D Slicer, COPDGene investigators evaluated over 3600 subjects' CT scans and found that airway wall thickness increased with bronchodilator responsiveness [21][22][23][24][25]. In a recent study of patients with NSCLC, Velazquez et al extracted volumetric data on NSCLC size using 3D Slicer extensions [26]. The ability to provide accurate tumor growth assessment allows more precise treatment response monitoring.…”
Section: Airway Inspectormentioning
confidence: 99%